2018
DOI: 10.1101/501585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensory Cue Combination in Children Under 10 Years of Age

Abstract: Cue combination occurs when two independent noisy perceptual estimates are merged together as a weighted average, creating a unified estimate that is more precise than either single estimate alone. Surprisingly, this effect has not been demonstrated compellingly in children under the age of 10 years, in contrast with the array of other multisensory skills that children show even in infancy. Instead, across a wide variety of studies, precision with both cues is no better than the best single cue – and sometimes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
2
4
1
Order By: Relevance
“…Thus, their data (in 7-to 10-year-old children) and our behavioral and modeling results for the VE (in 5-to 9-year-old children) suggest that children are capable to integrate auditory and visual spatial cues and that audio-visual localization does not reflect an unspecific visual bias or alternative strategies such as cue switching. In contrast to the present study, Negen et al [19] reported a precision advantage with bimodal stimuli as predicted by the MLE model, whereas the MLE model did not fit our data well. These authors told their participants that both the visual and the auditory stimulus indicated the location of a hidden character, which had to be localized.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, their data (in 7-to 10-year-old children) and our behavioral and modeling results for the VE (in 5-to 9-year-old children) suggest that children are capable to integrate auditory and visual spatial cues and that audio-visual localization does not reflect an unspecific visual bias or alternative strategies such as cue switching. In contrast to the present study, Negen et al [19] reported a precision advantage with bimodal stimuli as predicted by the MLE model, whereas the MLE model did not fit our data well. These authors told their participants that both the visual and the auditory stimulus indicated the location of a hidden character, which had to be localized.…”
Section: Discussioncontrasting
confidence: 99%
“…By contrast, the SW model was not able to explain the results of Experiment 1. These findings are in line with results from Negen et al [19], who recently reported that children under 10 years of age are able to integrate auditory and visual cues in an audio-visual spatial localization task. Thus, their data (in 7-to 10-year-old children) and our behavioral and modeling results for the VE (in 5-to 9-year-old children) suggest that children are capable to integrate auditory and visual spatial cues and that audio-visual localization does not reflect an unspecific visual bias or alternative strategies such as cue switching.…”
Section: Discussionsupporting
confidence: 93%
“…Here, we demonstrate the effect of a central tendency bias on estimates of the combination effect in previously published data. We re-analyzed the data from Experiment 1 in an article recently published in Cognition (Negen et al, 2019). This study presented 77 7-to 10-year-old children with audio, visual, or audio-visual cues to a horizontal location.…”
Section: An Example With Empirical Two-cue Continuous Response Datamentioning
confidence: 99%
“…Here, we demonstrate the effect of a central tendency bias on estimates of the combination effect in previously published data. We re-analysed the data from Experiment 1 in an article recently published in Cognition (Negen et al, 2019). This study presented 77 7-10 year old children with audio, visual, or audio-visual cues to a horizontal location.…”
Section: Introductionmentioning
confidence: 99%